ANALISIS POSTUR KERJA KARYAWAN KANTOR PADA PT XZ - Br Tarigan, Elisya Florena; Zetli, Sri (LPPM Universitas Putera Batam, 2021)
Ergonomics is a systematic branch of science to utilize information about human nature, human capabilities and limitations to design effective, safe and comfortable work systems. Ergonomics includes many things related to employee work, one of which is office ergonomics which includes the entire work environment and work tools related to computers, chairs and others. High demands for office employees at PT. XZ requires employees to work for quite a long time where based on existing surveys, it is found that office workers spend more than 75% of their working time sitting in front of the computer. Jobs like this are related to several ergonomic risks felt by employees, so it is necessary to measure the level of ergonomics risk in office employees at PT. XZ. Rapid Office Strain Assessment (ROSA) is a rapid analysis to measure work risks associated with the use of computers where this method of assessment is designed to measure the risk of worker injury and determine the level of change action based on reports of worker discomfort. From the results of the study it was found that complaints on the employee's body using the CMDQ questionnaire showed that 5 employees felt the most complaints in the lower back by 28.5%, the neck 21%, the upper back 18% and finally the hips / buttocks by 12 ,8%. From the analysis of work posture using the ROSA method, the final score of the five employees is the same, namely 5, which means that it is included in the warning level classification so that it is necessary to improve work posture according to the setting procedure for computer work stations, namely by paying attention to chair height, elbow position, monitor surface distance, monitor height, computer surface position, back and forth backrest, telephone distance, wrist angle, and mouse position.